Karakteristik Tekstur Brownies yang Dipanggang dengan Microwave dengan Penambahan Pati Termodifikasi - Medi Nova; Feri Kusnandar; Elvira Syamsir (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2015)
Microwave-baked brownies easily experiences high moisture loss and staling during storage. This research studied the effects of modified starch addition in the formula of brownies premix to the texture characteristics and staling inhibition of microwave-baked brownies during storage. Three types of modified starches, i.e. pregelatinized and crosslinked waxy corn starch (PIW), pregelatinized potato starch (PK), and pregelatinized or hydroxypropylated-substituted waxy corn (PHW) were tested. The microwave was set at medium-high heating temperature (90-95ºC, 600 watts) for 5 minutes. The texture characteristics (hardness, cohesiveness, adhesiveness)and sensory characteristics (pore of crumb, moistness, softness, density and overall acceptance) were evaluated during storage. Freshly microwave-baked brownies with the addition of starch PIW or PHW for 1% had excellent texture. However, brownies with the addition of starch PHW showed the most stable texture and least staling after three-day storege based on its moistness, density and overall acceptability. However, the product had softness for two-day storage.